2001
DOI: 10.1038/modpathol.3880457
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Islet Cell Tumor with Sarcomatous Differentiation

Abstract: Malignant mesenchymal neoplasms of the pancreas are rare and malignant islet cell tumors with sarcomatous dedifferentiation are rarer still. We present a case of malignant islet cell tumor with sarcomatous differentiation, which to our knowledge is only the second reported case showing such a combination of morphologic features. Clinically, the neoplasm was not hormonally active and immunohistochemical staining was negative for gastrin, glucagon, insulin and somatostatin. The sarcomatous component strongly rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…It recruits the coactivator b-catenin to enhancer elements of the genes and activates transcription of cyclin D1, c-jun, and c-myc (10), and its expression was observed in all the cell components. The clear cells were morphologically similar to the cells seen in subtypes of neuroendocrine tumor: clear cell type (11,12), spindle cell type (13), and neuroendocrine tumor with sarcomatoid differentiation (14). Immunohistochemical staining showed that the clear cells were positive for chromogranin A, synaptophysin, CD56, NSE, and AE1/AE3, indicating neuroendocrine differentiation of the cells.…”
Section: Commentsmentioning
confidence: 58%
“…It recruits the coactivator b-catenin to enhancer elements of the genes and activates transcription of cyclin D1, c-jun, and c-myc (10), and its expression was observed in all the cell components. The clear cells were morphologically similar to the cells seen in subtypes of neuroendocrine tumor: clear cell type (11,12), spindle cell type (13), and neuroendocrine tumor with sarcomatoid differentiation (14). Immunohistochemical staining showed that the clear cells were positive for chromogranin A, synaptophysin, CD56, NSE, and AE1/AE3, indicating neuroendocrine differentiation of the cells.…”
Section: Commentsmentioning
confidence: 58%